Land subdivision: A case study in metropolýtan area of Istanbul - Sevkiye Sence Turk (European Regional Science Association (ERSA), 2001)
The application of detailed urban plans is only possible by realizing subdivision in urban areas. Minor subdivisions, land readjustment projects and expropriations in Turkey are primary methods in realizing subdivision of urban areas. Municipalities are responsible for the application of detailed urban plans. In metropolitan areas this power is given to sub-municipalities. The purpose of this paper is to determine whether or not to be difference in realizing of subdivision according to detailed urban plans between urban areas in Istanbul Metropolitan Area. The other purpose of this paper is to constitute a model concerning realizing of subdivision according to detailed urban planning for urban areas in different population groups in Istanbul Metropolitan Area and then to compare each these city groups. For this research a sample survey method were used were questionnaires were sent to Municipalities of urban areas in different population groups in Istanbul Metropolitan Area. In addition, the realizing of subdivision ýndex (RSI) are used as a dependent variable and population, population growth rate, global density in urban areas according to detailed plans, municipal budgets, socio-economic index, the average of land values of cities. Multiple Regression Model is used for each city groups.
Keywords: 330